Gabapentin Toxicity and Role of Dialysis; Case Series and Literature Review (Journal of Renal and Hepatic Disorders, 2021)
Gabapentin is frequently used as an analgesic in patients with chronic kidney disease (CKD). It is excreted exclusively through kidney, and therefore impairment in kidney function could lead to gabapentin accumulation and hence toxicity. We present our experience of 3 cases with Gabapentin toxicity who were managed according to the severity of symptoms. Case 1: A 32-year-old male was found lying unconscious after consuming around 12,000 mg of gabapentin and had respiratory depression, rhabdomyolysis, and acute kidney injury (AKI). Patient was managed with supportive care and hemodialysis (HD). Case 2: A 64-year-old male CKD Stage 5 (5D) patient with diabetic neuropathy was started on gabapentin 300 mg daily by his primary care physician 1 week back. Patient started to feel sleepy and developed altered sensorium and myoclonus. Discontinuation of gabapentin and a session of HD led to dramatic improvement in patient’s status. Case 3: A 70-year-old female diabetic patient with CKD Stage 3 and had diabetic neuropathy. Her neuropathic symptoms had improved with gabapentin 300 mg twice daily, but lately patient was feeling sleepy during the day and was confused. Discontinuation of the drug led to improvement in symptoms. Gabapentin is a relatively safe medication, but in certain clinical scenarios, particularly in impaired renal functions, can lead to severe complications. Moreover, it per se can rarely lead to rhabdomyolysis and AKI. Clinical suspicion and timely decontamination are needed, and sometimes dialytic therapy may be needed.
Keywords: dialysis; gabapentin; myoclonus